Scalable urban tree canopy modelling for Canadian cities - Bayan F. Shaeri; Yuhao Lu; Alexander J.F. Martin; Lukas G. Olson; Raphael Ayambire; Txomin Hermosilla; Lucila M. Corro; Jay E. Diffendorfer; Peter C. Ibsen (Urban Forestry & Urban Greening, 2026)

The influence of tree canopy cover data choices on urban ecosystem accounting - Levi T. Sweet-Breu; Gregory S. Cermak; Lucila M. Corro; Peter C. Ibsen; Mehdi P. Heris; Raimundo Atal; Ryan A. McManamay; Jay E. Diffendorfer; Kenneth J. Bagstad (Ecosystem Services, 2026)

Urban tree cover provides consistent mitigation of extreme heat in arid but not humid cities - Peter C. Ibsen; Benjamin R. Crawford; Lucila M. Corro; Kenneth J. Bagstad; Brandon E. McNellis; George D. Jenerette; Jay E. Diffendorfer (Sustainable Cities and Society, 2024)

The interplay of future solar energy, land cover change, and their projected impacts on natural lands and croplands in the US - Jay E. Diffendorfer; Brian Sergi; Anthony Lopez; Travis Williams; Michael Gleason; Zach Ancona; Wesley Cole (Science of The Total Environment, 2024)

The geographic extent of bird populations affected by renewable‐energy development - Hannah B. Vander Zanden; David M. Nelson; Tara J. Conkling; Taber D. Allison; Jay E. Diffendorfer; Thomas V. Dietsch; Amy L. Fesnock; Scott R. Loss; Patricia A. Ortiz; Robin Paulman; Krysta H. Rogers; Peter M. Sanzenbacher; et al. (Conservation Biology, 2024)
Bird populations are declining globally. Wind and solar energy can reduce emissions of fossil fuels that drive anthropogenic climate change, yet renewable‐energy production represents a potential threat to bird species. Surveys to assess potential effects at renewable‐energy facilities are exclusively local, and the geographic extent encompassed by birds killed at these facilities is largely unknown, which creates challenges for minimizing and mitigating the population‐level and cumulative effects of these fatalities. We performed geospatial analyses of stable hydrogen isotope data obtained from feathers of 871 individuals of 24 bird species found dead at solar‐ and wind‐energy facilities in California (USA). Most species had individuals with a mix of origins, ranging from 23% to 98% nonlocal. Mean minimum distances to areas of likely origin for nonlocal individuals were as close as 97 to >1250 km, and these minimum distances were larger for species found at solar‐energy facilities in deserts than at wind‐energy facilities in grasslands (Cohen's d = 6.5). Fatalities were drawn from an estimated 30–100% of species’ desingated ranges, and this percentage was significantly smaller for species with large ranges found at wind facilities (Pearson's r = −0.67). Temporal patterns in the geographic origin of fatalities suggested that migratory movements and nonmigratory movements, such as dispersal and nomadism, influence exposure to fatality risk for these birds. Our results illustrate the power of using stable isotope data to assess the geographic extent of renewable‐energy fatalities on birds. As the buildout of renewable‐energy facilities continues, accurate assessment of the geographic footprint of wildlife fatalities can be used to inform compensatory mitigation for their population‐level and cumulative effects.

Mapping development preferences on the perceived value of ecosystem services and land use conflict and compatibility in Greater Kuala Lumpur - Karen T. Lourdes; Chris N. Gibbins; Ben C. Sherrouse; Darius J. Semmens; Perrine Hamel; Ruzana Sanusi; Badrul Azhar; Jay Diffendorfer; Alex M. Lechner (Urban Forestry & Urban Greening, 2024)

Potential economic consequences along migratory flyways from reductions in breeding habitat of migratory waterbirds - Wayne E. Thogmartin; James H. Devries; Darius J. Semmens; Jay E. Diffendorfer; James A. Dubovsky; Jonathan J. Derbridge; Brady J. Mattsson (Biological Conservation, 2023)

Limitations, lack of standardization, and recommended best practices in studies of renewable energy effects on birds and bats - Tara J. Conkling; Scott R. Loss; Jay E. Diffendorfer; Adam E. Duerr; Todd E. Katzner (Conservation Biology, 2021)
Increasing global energy demand is fostering the development of renewable energy as an alternative to fossil fuels. However, renewable energy facilities may adversely affect wildlife. Facility siting guidelines recommend or require project developers complete pre‐ and postconstruction wildlife surveys to predict risk and estimate effects of proposed projects. Despite this, there are no published studies that have quantified the types of surveys used or how survey types are standardized within and across facilities. We evaluated 628 peer‐reviewed publications, unpublished reports, and citations, and we analyzed data from 525 of these sources (203 facilities: 193 wind and 10 solar) in the United States and Canada to determine the frequency of pre‐ and postconstruction surveys and whether that frequency changed over time; frequency of studies explicitly designed to allow before‐after or impact‐control analyses; and what types of survey data were collected during pre‐ and postconstruction periods and how those data types were standardized across periods and among facilities. Within our data set, postconstruction monitoring for wildlife fatalities and habitat use was a standard practice ( n = 446 reports), but preconstruction estimation of baseline wildlife habitat use and mortality was less frequently reported ( n = 84). Only 22% ( n = 45) of the 203 facilities provided data from both pre‐ and postconstruction, and 29% ( n = 59) had experimental study designs. Of 108 facilities at which habitat‐use surveys were conducted, only 3% estimated of detection probability. Thus, the available data generally preclude comparison of biological data across construction periods and among facilities. Use of experimental study designs and following similar field protocols would improve the knowledge of how renewable energy affects wildlife. Article Impact Statement Many surveys at wind and solar facilities provide limited information on wildlife use and fatality rates.

Quantitative tools for implementing the new definition of significant portion of the range in the U.S. Endangered Species Act - Julia E. Earl; Sam Nicol; Ruscena Wiederholt; Jay E. Diffendorfer; Darius Semmens; D. T. Tyler Flockhart; Brady J. Mattsson; Gary McCracken; D. Ryan Norris; Wayne E. Thogmartin; Laura López‐Hoffman (Conservation Biology, 2018)
In 2014, the Fish and Wildlife Service (FWS) and National Marine Fisheries Service announced a new policy interpretation for the U.S. Endangered Species Act (ESA). According to the act, a species must be listed as threatened or endangered if it is determined to be threatened or endangered in a significant portion of its range (SPR). The 2014 policy seeks to provide consistency by establishing that a portion of the range should be considered significant if the associated individuals’ “removal would cause the entire species to become endangered or threatened.” We reviewed 20 quantitative techniques used to assess whether a portion of a species’ range is significant according to the new guidance. Our assessments are based on the 3R criteria—redundancy (i.e., buffering from catastrophe), resiliency (i.e., ability to withstand stochasticity), and representation (i.e., ability to evolve)—that the FWS uses to determine if a species merits listing. We identified data needs for each quantitative technique and considered which methods could be implemented given the data limitations typical of rare species. We also identified proxies for the 3Rs that may be used with limited data. To assess potential data availability, we evaluated 7 example species by accessing data in their species status assessments, which document all the information used during a listing decision. In all species, an SPR could be evaluated with at least one metric for each of the 3Rs robustly or with substantial assumptions. Resiliency assessments appeared most constrained by limited data, and many species lacked information on connectivity between subpopulations, genetic variation, and spatial variability in vital rates. These data gaps will likely make SPR assessments for species with complex life histories or that cross national boundaries difficult. Although we reviewed techniques for the ESA, other countries require identification of significant areas and could benefit from this research.

Optimizing conservation strategies for Mexican free-tailed bats: a population viability and ecosystem services approach - Ruscena Wiederholt; Laura López-Hoffman; Colleen Svancara; Gary McCracken; Wayne Thogmartin; Jay E. Diffendorfer; Brady Mattson; Kenneth Bagstad; Paul Cryan; Amy Russell; Darius Semmens; Rodrigo A. Medellín (Biodiversity and Conservation, 2015)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)